Co-Operation between Technical Education of University and Electro-Technical Standardization Association - Hieta-Wilkman, S.; Vesa, J.; Korpinen, L. (Elektronika ir Elektrotechnika, 2010)
This paper discusses the three educational cooperation projects between Tampere University of Technology, Vaasa University and standardization bodies – especially Electrotechnical Standardization Organization SESKO in Finland. The projects are Measuring Technology Course, standardization website to educational institution and the course of SF6 gas questions. The aim of cooperation is to improve readiness of students for work life. The two purposes are 1) to improve knowledge of technical students about their line-specific standards and standardization of their own general area. 2) to support the teachers through familiarization of standards and by using standards as instruments of teaching. Feedback from the students and teachers was quite positive.